2013
DOI: 10.1111/imb.12064
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression profiling of odorant‐binding proteins in the tarnished plant bug, Lygus lineolaris

Abstract: In insects, the perception and discrimination of odorants requires the involvement of odorant-binding proteins (OBPs). To gain a better molecular understanding of olfaction in the agronomic pest Lygus lineolaris (the tarnished plant bug), we used a transcriptomics-based approach to identify potential OBPs. In total, 33 putative OBP transcripts, including the previously reported Lygus antennal protein (LAP), were identified based on the characteristic OBP Cys signature and/or sequence similarity with annotated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 94 publications
5
78
1
2
Order By: Relevance
“…Thus, we cannot rule out the possibility that RproOBP26 might be involved in the transport of non-sensorial molecules in the gut, as well as semiochemicals in antennae. Although, only one gene for RproOBP26 has been annotated in the genome (Mesquita et al, 2015), we could not exclude the possibility of RproOBP26 has alternative splicing, as previously observed for other insect species (Forêt and Maleszka, 2006; Hull et al, 2014). …”
Section: Discussionmentioning
confidence: 78%
“…Thus, we cannot rule out the possibility that RproOBP26 might be involved in the transport of non-sensorial molecules in the gut, as well as semiochemicals in antennae. Although, only one gene for RproOBP26 has been annotated in the genome (Mesquita et al, 2015), we could not exclude the possibility of RproOBP26 has alternative splicing, as previously observed for other insect species (Forêt and Maleszka, 2006; Hull et al, 2014). …”
Section: Discussionmentioning
confidence: 78%
“…OBP and CSP gene expression in the proboscis has been observed in other insects including Apolygus lucorum (Hua et al, 2012), Lygus lineolaris (Hull, Perera & Snodgrass, 2014), S. podoptera (Liu et al, 2015c), and A. dissimilis (Sun et al, 2016). Further functional studies have also confirmed the gustation function of some genes: OBP49a in D. melanogaster is involved in the suppression of sweet taste by bitter chemicals (Jeong et al, 2013); some OBPs in D. melanogaster can modulate sucrose intake in response to a panel of nine bitter compounds by RNAi-mediated methods (Swarup et al, 2014); and CSP4, which is exclusively presented in the proboscis of two sibling species— H. armigera and H. assulta —an act as a wetting agent to reduce the surface tension of aqueous solutions (Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…lugens [22], and 21 of 33 OBPs in L . lineolaris [19]. Seven of 13 SaveOBPs ( SaveOBP6 , SaveOBP7 , SaveOBP9 , SaveOBP10 , SaveOBP13 , SaveOBP14 and SaveOBP15 ) were uniquely or primarily expressed in antennae compared with other tissues, indicating a vital olfactory role for these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequencing facilitated the identification of 15 OBP genes in the hemipteran Acyrthosiphon pisum [18]. In contrast, mRNA-based transcriptome sequencing has led to the discovery of numerous OBPs from diverse hemipteran pests including Lygus lineolaris [19], Adelphocoris lineolatus [20], Aphis gossypii [21], Nilaparvata lugens [22, 23], Sogatella furcifera [24], and Apolygus lucorum [25]. Interestingly, the number of OBPs reported has differed depending on the species (eg.…”
Section: Introductionmentioning
confidence: 99%